"بیوعات میں قیاس پر استحسان کی ترجیح: فقہی جزئیات کا تجزیاتی و تطبیقی مطالعہ": "THE PREFERENCE OF ISTIHSAN OVER QIYAS IN COMMERCIAL TRANSACTIONS: AN ANALYTICAL AND APPLIED STUDY OF JURISTIC DETAILS" (Al-Aasar, 2026)
This research article examines the concept of Istihsan (juristic preference) within Islamic jurisprudence and highlights its significance in deriving legal rulings, particularly within the Hanafi school of thought. The study begins with a conceptual introduction to Istihsan and discusses its juristic definition and methodological foundations. It then analyzes the legal status of Istihsan in the context of the four major Sunni schools of law, presenting the perspectives of the Hanafi, Maliki, Shafi‘i, and Hanbali jurists with references from primary classical sources.Furthermore, the article explores various juristic applications of Istihsan in practical legal matters, demonstrating how this principle helps address complex social realities and provides flexibility within Islamic law. Through selected examples from fiqh literature, the study illustrates the role of Istihsan in facilitating ease, preventing hardship, and ensuring justice in legal rulings.Finally, a comparative analysis of the four schools is presented, showing that although the terminology and methodological acceptance of Istihsan differ among the jurists, its practical spirit is reflected in their legal reasoning in various forms. The research concludes that Istihsan serves as an important juristic tool that strengthens the adaptability and dynamism of Islamic law in changing circumstances.